Underpricing of New Issues Listed on the Second Board of the Kuala Lumpur Stock Exchange During 1989 to 1994 - Ooi, Eng Hong (1997)
This paper studies the underpricing of Initial Public Offerings ("IPOs") listed on the Second Board of the Kuala Lumpur Stock Exchange ("KLSE") during 1 989 to 1 994. The results show that the average return, based on the difference between the first day closing price and the offer price, is approximately 65%. However, the returns after the first day up-to the first month of listing normally decline, even though there are not significantly difference from the returns received on the first day of listing. During the third month of listing, the underpricing becomes larger and this continues up-to the third year, where the average underpricing is 251 %. It is clear from this study that the new issues are mostly underpriced. In this study, the relationships between level of underpricing and other variables like underwriters and auditors involved in the IPOs, the size of public issues and the nature of business of the listing company are also studied.